The Impact Of Economic Openness Degree On Economic Growth Rate(The State Of Syria) For The Period 1980-2010 (Latakia University Journal - Economic and Legal Sciences Series, 2020)
In this article the researcher tried to navigate the impact of economic openness degree on the economic growth rate in Syria for the period 1980-2010, so the researcher studied the definition of the open and closed economies, then compared them theoretically, then the researcher studied the time series data that represents the major economic openness degree indexes from 1980 to 2010.After the statistical study the researcher found that the relation between the economic openness degree and the gross domestic product is significant and positive in the period 2000-2010, and this period has the highest economic openness degree in the Syrian economic history from the 1980s, and the main reason for this is the political wellness to enhance the economy and rising the economic growth rates, by a number of  legislative decrees like the legislative decree number 7 issued by Mr. president Bashar Hafez Al Assad  in 13/5/2000.